Antimicrobial activity of a new compound of 1,2,4-triazole derivatives against pathogens of poultry bacterial diseases - Vashchyk, Yevheniia; Safonov, Andriy; Zakhariev, Andriy; Shapovalova, Olga; Demianenko, Denys (ScienceRise: Biological Science, 2024)
The aim: study of the antimicrobial activity of a new compound of 1,2,4-triazole derivatives against pathogens of poultry bacteriosis. Materials and methods. Research was conducted on the bactericidal activity of a new compound of 1,2,4-triazole derivatives against pathogens of poultry bacteriosis. Dimethylsulfoxide was used to dissolve the ASP compound. In order to study the bactericidal activity of the compounds, reference and field strains of S. typhimurium, E. coli, St. aureus, P. aeruginosa, P. vulgaris, K. pneumoniae, L. monocytogenes, E. faecalis were used. The study of the minimum inhibitory concentration (MIC) was carried out by the method of serial dilution in Muller-Hinton broth, the minimum bactericidal concentration (MBC) - by seeding from transparent tubes on Petri dishes with differential nutrient media. The results. The inhibitory effect of the ASP compound at a concentration of 62.5 μg/ml against E. coli, L. Monocytogenes, E. faecalis, and at a concentration of 125 μg/ml against S. typhimurium, E. coli, St. aureus, P. aeruginosa, P. vulgaris, K. pneumoniae, L. monocytogenes, E. faecalis was established. The bactericidal effect of the ASP compound was detected at a concentration of 62.5 μg/ml against L. monocytogenes, at a concentration of 125 μg/ml - against E. coli, St. aureus, L. monocytogenes and E. faecalis. The ASP compound at a concentration of 250 μg/ml has the inhibitory and bactericidal effect on all tested reference and field strains of poultry bacteriosis pathogens. Conclusions. A new synthesized compound of 1,2,4 triazole derivatives of ASP exhibits the inhibitory effect at a concentration of 125 μg/ml - in relation to E. coli, St. aureus, L. monocytogenes and E. faecalis and the bactericidal effect against bacteriosis pathogens S. typhimurium, E. coli, St. aureus, P. aeruginosa, P. vulgaris, K. pneumoniae, L. monocytogenes, E. faecalis at a concentration of 250 μg/ml